The Effectiveness of Solid Waste Extract from Lemongrass (Cymbopogon citratus) as a Bioinsecticide for Controlling Whitefly (Bemisia tabaci) Pests on Pomelo Plants - Tristiyanti, Alvia Sefie; Hayani, Alfitra; Ardianto, Sandi Dimas; Kurniasari, Laeli (Journal of Biotechnology and Natural Science, 2023)
This research aims to analyze the effect of lemongrass waste extract on the mortality of whitefly and determine the optimal concentration of lemongrass waste extract to eradicate whiteflies within 24 hours. Lemongrass waste extract (leaves and stems) can be obtained through extraction using maceration. The waste is dried and ground to 60 mesh, then dissolved in 96% ethanol and ethyl acetate solvents at a ratio of 1:8 (w/v). Extraction is carried out over variable times of 2, 4, and 6 days. The optimal results are then used to create concentrations by dissolving 250 ml of distilled water in the mother solution, resulting in test solutions of 0, 200, 400, 800, and 1200 mg/L. Observations on the treatments are conducted after 24 hours, and the number of dead whiteflies is counted. Subsequently, the mortality of the whiteflies is analyzed. Based on the research findings, the highest mortality percentage after 24 hours is observed in the ethanol extract, with a dose of 1200 mg/L at 81.81%. After determining the mortality rates, probit analysis is conducted to determine the LC50 (Lethal Concentration 50) value. The optimal concentration for ethanol extract is found to be 1200 mg/L, with an LC50 of 885.102 mg/L. This indicates that lemongrass waste extract is moderately toxic to whiteflies.